Disruptive effects of plasticizers bisphenol A, F, and S on steroidogenesis of adrenocortical cells - Pötzl, Benedikt; Kürzinger, Lydia; Kendl, Sabine; Stopper, Helga; Kurlbaum, Max; Fassnacht, Martin; Dischinger, Ulrich (Frontiers in Endocrinology, 2024)
Introduction: Endocrine disrupting chemicals (EDCs) are known to interfere with endocrine homeostasis. Their impact on the adrenal cortex and steroidogenesis has not yet been sufficiently elucidated. This applies in particular to the ubiquitously available bisphenols A (BPA), F (BPF), and S (BPS). Methods: NCI-H295R adrenocortical cells were exposed to different concentrations (1nM-1mM) of BPA, BPF, BPS, and an equimolar mixture of them (BPmix). After 72 hours, 15 endogenous steroids were measured using LC-MS/MS. Ratios of substrate and product of CYP-regulated steps were calculated to identify most influenced steps of steroidogenesis. mRNA expression of steroidogenic enzymes was determined by real-time PCR. Results: Cell viability remained unaffected at bisphenol concentrations lower than 250 µM. All tested bisphenols and their combination led to extensive alterations in the quantified steroid levels. The most profound fold changes (FC) in steroid concentrations after exposure to BPA (>10µM) were seen for androstenedione, e.g. a 0.37±0.11-fold decrease at 25µM (p≤0.0001) compared to vehicle-treated controls. For BPF, levels of 17-hydroxyprogesterone were significantly increased by 25µM (FC 2.57±0.49, p≤0.001) and 50µM (FC 2.65±0.61, p≤0.0001). BPS treatment led to a dose-dependent decrease of 11-deoxycorticosterone at >1µM (e.g. FC 0.24±0.14, p≤0.0001 at 10µM). However, when combining all three bisphenols, additive effects were detected: e.g. 11-deoxycortisosterone was decreased at doses >10µM (FC 0.27±0.04, p≤0.0001, at 25µM), whereas 21-deoxycortisol was increased by 2.92±0.20 (p≤0.01) at 10µM, and by 3.21±0.45 (p≤0.001) at 50µM. While every measured androgen (DHEA, DHEAS, androstenedione, testosterone, DHT) was lowered in all experiments, estradiol levels were significantly increased by BPA, BPF, BPS, and BPmix (e.g. FC 3.60±0.54, p≤0.0001 at 100µM BPF). Calculated substrate-product ratios indicated an inhibition of CYP17A1-, and CYP21A2 mediated conversions, whereas CYP11B1 and CYP19A1 showed higher activity in the presence of bisphenols. Based on these findings, most relevant mRNA expression of CYP genes were analysed. mRNA levels of StAR, CYP11B1, and CYP17A1 were significantly increased by BPF, BPS, and BPmix. Discussion: In cell culture, bisphenols interfere with steroidogenesis at non-cytotoxic levels, leading to compound-specific patterns of significantly altered hormone levels. These results justify and call for additional in-vivo studies to evaluate effects of EDCs on adrenal gland functionality.